New autoantibodies in the diagnosis of rheumatoid arthritis - Kuligowska, Magdalena; Odrowąż-Sypniewska, Grażyna; Krintus, Magdalena (Reumatologia/Rheumatology, 2007)
Rheumatoid arthritis (RA) is the most common inflammatory joint disease. The diagnosis of this disease, despite established criteria, still creates many difficulties, especially in the early stage of the disease. The sensitivity of rheumatoid factor (RF) in the initial phase of disease is too low and the relatively late occurrence of radiological changes means that searching for new markers with high sensitivity and specificity useful in laboratory diagnosis of RA is highly appreciated. Among serological parameters special attention has been focused on anti-cyclic citrullinated peptide antibodies (anti-CCP), antikeratin antibodies (AKA), antifilaggrin antibodies (AFA) and antiperinuclear factor (APF). However, for high specificity and sensitivity, anti-CCP seem to be the most useful in diagnosis of RA. Anti-CCP will be available very soon in an automatic immunological analyzer enabling the detection of these antibodies in routine laboratories.